Electrochemical performance of Na2Ti3O7/C negative electrode in ionic liquid electrolyte for sodium secondary batteries - Ding, Changsheng; Nohira, Toshiyuki; Hagiwara, Rika (Journal of Power Sources, 2017)
In this study, carbon-coated Na2Ti3O7 (Na2Ti3O7/C) is synthesized by a solid-state reaction method, and its charge-discharge characteristics as a negative electrode material in an ionic liquid electrolyte, Na[FSA]-[C3C1pyrr][FSA] (FSA = bis(fluorosulfonyl)amide; C3C1pyrr = N-methyl-N-propylpyrrolidinium), are investigated at 363 K. The Na2Ti3O7/C negative electrode shows an initial discharge capacity of 215 mAh (g-Na2Ti3O7/C)−1 at a current rate of 20 mA (g-Na2Ti3O7/C)−1 in the voltage range 0.01–2.5 V. The high discharge capacity of the Na2Ti3O7/C negative electrode is attributed to the high operation temperature in the Na[FSA]-[C3C1pyrr][FSA] ionic liquid electrolyte. Although high discharge capacity is achieved, the Na2Ti3O7/C negative electrode shows relatively poor cycle performance because of the irreversible insertion of some Na ions and the formation of cracks. •Na2Ti3O7/C negative electrode was investigated in ionic liquid electrolyte.•The Na2Ti3O7/C electrode showed a high reversible capacity of 215 mAh g−1 at 363 K.•The formation of Na4.8Ti3O7 is suggested in the charged Na2Ti3O7/C electrode.•Some Na irreversible insertion and crack formation result in capacity degradation.